Otoplasty Online Information: A Comprehensive Analysis of the Websites and Videos that Patients View Regarding Cosmetic Ear Surgery - Nissan, Michael E.; Gupta, Amar; Rayess, Hani; Black, Kevin Z.; Carron, Michael (Facial Plastic Surgery, 2018)
Physicians should be aware of both websites and videos available online regarding the otoplasty procedure to provide quality care. This study systematically analyzes the authorships, reliability, quality, and readability of the websites, as well as the authorships and primary objectives of the videos regarding otoplasty. Validated instruments were used to analyze the reliability, quality, and readability of websites, and videos were systematically categorized and analyzed. A Google search was conducted, and the first five pages of results were included in this study. After excluding unrelated websites, the remaining 44 websites were categorized by authorship (physician, patient, academic, or unaffiliated) and were analyzed using the validated DISCERN instrument for reliability and quality, as well as various other validated instruments to measure readability. A YouTube search was also conducted, and the first 50 relevant videos were included in the study. These videos were categorized by authorship and their primary objective. Website authorships were physician-dominated. Reliability, quality, and overall DISCERN score differ between the four authorship groups by a statistically significant margin (Kruskall–Wallis test, p < 0.05). Unaffiliated websites were the most reliable, and physician websites were the least reliable. Academic websites were of the highest quality, and patient websites were of the lowest quality. Readability did not differ significantly between the groups, though the readability measurements made showed a general lack of material easily readable by the general public. YouTube was likewise dominated by physician-authored videos. While the physician-authored videos sought mainly to inform and to advertise, patient-authored videos sought mainly to provide the patient's perspective. Academic organizations showed very little representation on YouTube, and the YouTube views on otoplasty videos were dominated by the top 20 videos, which represented over 93% of the total views of videos included in this study.
Keywords: otoplasty; DISCERN; readability; websites; videos; online information; patient education; Google; YouTube